2004
DOI: 10.1095/biolreprod.103.021048
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PEPP Homeobox Gene, TOX, Is Highly Glutamic Acid Rich and Specifically Expressed in Murine Testis and Ovary1

Abstract: The homeobox gene superfamily has been highly conserved throughout evolution. These genes act as transcription factors during several important developmental processes. To explore the functional roles of homeobox genes in spermatogenesis, we performed a degenerate oligonucleotide polymerase chain reaction (PCR) screening of a testis cDNA library and isolated a novel mouse homeobox gene. This gene, which we named Tox, encodes a homeodomain protein distantly related to members of the Paired/Pax (Prd/Pax) family.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…While it is not clear what selective forces are responsible for the recent amplification of these three genes in mice, it is clear that most of these paralogs are expressed and all but one (Rhox3d) encode full-length proteins and thus are presumably functional (Jackson et al 2006, Morris et al 2006, Wang & Zhang 2006. The b subcluster has five genes, including the founding Rhox family member -Rhox5 -and three other genes that had previously been given other names: Rhox6 (Psx1), Rhox8 (Tox), and Rhox9 (Psx2 and Gpbox) (Chun et al 1999, Takasaki et al 2000, Kang et al 2004. The g subcluster was originally defined as having three genes (MacLean et al 2005a), but recently, a fourth member has been identified: Rhox13 (Geyer & Eddy 2008).…”
Section: The Rhox Gene Clustermentioning
confidence: 99%
“…While it is not clear what selective forces are responsible for the recent amplification of these three genes in mice, it is clear that most of these paralogs are expressed and all but one (Rhox3d) encode full-length proteins and thus are presumably functional (Jackson et al 2006, Morris et al 2006, Wang & Zhang 2006. The b subcluster has five genes, including the founding Rhox family member -Rhox5 -and three other genes that had previously been given other names: Rhox6 (Psx1), Rhox8 (Tox), and Rhox9 (Psx2 and Gpbox) (Chun et al 1999, Takasaki et al 2000, Kang et al 2004. The g subcluster was originally defined as having three genes (MacLean et al 2005a), but recently, a fourth member has been identified: Rhox13 (Geyer & Eddy 2008).…”
Section: The Rhox Gene Clustermentioning
confidence: 99%
“…PBX family 4 protein [ID: T4-844] is present in pachytene spermatocytes (Wagner et al, 2001). A member of the PEPP subfamily of paired-like homeobox proteins called TOX [ID: T4-845] is expressed in spermatids and sperm and is highly glutamic acid enriched (Kang et al, 2004). Hox gene family member A4 protein [ID: T4-846] is present at high levels in meiotic and postmeiotic germ cells but KOs are viable and fertile (Horan et al, 1994;Rubin et al, 1986;Wolgemuth et al, 1987).…”
Section: Homeobox Factorsmentioning
confidence: 99%
“…Pbx4, which is a Pbx family gene that is involved in axial patterning and organogenesis, is expressed in the testis, specifically in spermatocytes at the pachytene stage of the first meiotic prophase [42]. The Paired/Pax family homeobox gene Tox is expressed in the spermatid and spermatozoa of adult mice [43]. While studies have reported the presence of the messenger RNAs for these homeobox genes in germ cells, their functions in gene regulation are largely unknown.…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%